2010
DOI: 10.1186/1475-2840-9-59
|View full text |Cite
|
Sign up to set email alerts
|

Prediction model for high glycated hemoglobin concentration among ethnic Chinese in Taiwan

Abstract: BackgroundThis study aimed to construct a prediction model to identify subjects with high glycated hemoglobin (HbA1c) levels by incorporating anthropometric, lifestyle, clinical, and biochemical information in a large cross-sectional ethnic Chinese population in Taiwan from a health checkup center.MethodsThe prediction model was derived from multivariate logistic regression, and we evaluated the performance of the model in identifying the cases with high HbA1c levels (> = 7.0%). In total 17,773 participants (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Thirteen studies were conducted in Asian [ 7 20 21 22 23 24 25 26 27 28 29 30 31 ], eight in Caucasian [ 5 19 32 33 34 35 36 37 ] and four in multi-ethnic [ 38 39 40 41 ] populations. However, only two [ 39 40 ] of these multi-ethnic studies reported the ethnic groups represented, and both had more than 70% Caucasians.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen studies were conducted in Asian [ 7 20 21 22 23 24 25 26 27 28 29 30 31 ], eight in Caucasian [ 5 19 32 33 34 35 36 37 ] and four in multi-ethnic [ 38 39 40 41 ] populations. However, only two [ 39 40 ] of these multi-ethnic studies reported the ethnic groups represented, and both had more than 70% Caucasians.…”
Section: Resultsmentioning
confidence: 99%
“…Included studies had different T2DM definitions: seventeen studies (69%) had models predicting risk of undiagnosed T2DM [ 5 19 20 21 22 24 25 26 27 28 30 31 32 33 35 38 41 ], four studies (15%) predicted risk of undiagnosed and impaired glucose regulation [ 34 36 39 40 ], one study predicted risk of abnormally high HbA1c values [ 23 ], one study predicted the risk of prevalent T2DM [ 37 ], and two studies (8%) developed models predicting risk of both prevalent (including undiagnosed) T2DM [ 7 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Further follow-up analysis will be undertaken to fully evaluate the predictive value of these markers using a prediction model as was used by Chien et al [42]. …”
Section: Discussionmentioning
confidence: 99%
“…All participants provided written informed consent with the study protocol being reported elsewhere [18-20]. In brief, details of socioeconomic status, along with medical and medication histories were collected by questionnaires, and standardized clinical procedures were undertaken.…”
Section: Methodsmentioning
confidence: 99%